Developing deep group reflection within a Critical Reflection Action Learning set. (1st September 2016) - Shepherd, Gary
ABSTRACT: This account of practice describes how a manufacturing company in the North of England transformed their approach to problem-solving and action through the use of a Critical Reflection Action Learning (CRAL) methodology. The company, who had been in business for over 25 years, experienced problems due to a diminishing customer base and substantial changes in customers' buying behaviour. The account presented here is based on a 12-session CRAL project I carried out as part of my Ph.D. Research at the University of Hull Business School [Shepherd, G. 2011. "An Inductive Exploration of Group Learning and Knowledge Generation through Group Reflection and Psychoanalysis." PhD Thesis, University of Hull Business School]. This paper describes how the organisation changed the way in which they tackled complex, messy problems through the adoption of a CRAL technique using their own hand-drawn images as the focus for their individual, group and critical reflective efforts. As the action learning set improved their reflective practice, the group began to understand and untangle the complex links between the problems they were experiencing and the way in which the business environment had changed. The group completed the project with a more nuanced appreciation of the problems they experienced and developed their own unique problem-solving style, which mixed reflective questioning with emotional honesty.